Mobile element variation contributes to population-specific genome diversification, gene regulation and disease risk - Kojima, Shohei; Koyama, Satoshi; Ka, Mirei; Saito, Yuka; Parrish, Erica H.; Endo, Mikiko; Takata, Sadaaki; Mizukoshi, Misaki; Hikino, Keiko; Takeda, Atsushi; Gelinas, Asami F.; Heaton, Steven M.; et al. (Nature genetics, 2023)
Mobile genetic elements (MEs) are heritable mutagens that recursively generate structural variants (SVs). ME variants (MEVs) are difficult to genotype and integrate in statistical genetics, obscuring their impact on genome diversification and traits. We developed a tool that accurately genotypes MEVs using short-read whole-genome sequencing (WGS) and applied it to global human populations. We find unexpected population-specific MEV differences, including an Alu insertion distribution distinguishing Japanese from other populations. Integrating MEVs with expression quantitative trait loci (eQTL) maps shows that MEV classes regulate tissue-specific gene expression by shared mechanisms, including creating or attenuating enhancers and recruiting post-transcriptional regulators, supporting class-wide interpretability. MEVs more often associate with gene expression changes than SNVs, thus plausibly impacting traits. Performing genome-wide association study (GWAS) with MEVs pinpoints potential causes of disease risk, including a LINE-1 insertion associated with keloid and fasciitis. This work implicates MEVs as drivers of human divergence and disease risk. MEGAnE is a new tool to detect and genotype mobile element variants (MEVs) from short-read whole-genome sequencing datasets. Genetic analyses implicate MEVs as population-specific drivers of gene expression variation and disease risk.